2012
DOI: 10.3109/09513590.2012.692222
|View full text |Cite
|
Sign up to set email alerts
|

Autoimmune polyglandular syndrome: an unusual presentation with empty sella, premature ovarian failure, and Hashimoto’s thyroiditis associated with thyroid cancer

Abstract: Autoimmune polyglandular syndromes are rare disorders characterized by failure of several endocrine glands, as well as non-endocrine organs, associated with immune-mediated tissue destruction. We report a rare case of polyglandular syndrome type II in a patient who presented with premature ovarian failure, Hashimoto's thyroiditis and empty sella associated with a diagnosis of differentiated thyroid carcinoma. This case probably represents the first report on this tumor in a patient with polyglandular disorder.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Cases of papillary thyroid cancer in patients with APS including thyroiditis may prove interesting with this view, representing disease models with potential clues for scientific research. Besides the patient described by Karavanaki et al (1) and the case we described, we found in the literature another report suggesting the association between papillary thyroid cancer and APS type II (10) . Moreover, it is also worth pointing out that patients with APS type I/II have a nonsignificant increased mortality rate for thyroid cancer, approximately two-fold that expected in healthy subjects (11) .…”
Section: To the Editorsupporting
confidence: 68%
“…Cases of papillary thyroid cancer in patients with APS including thyroiditis may prove interesting with this view, representing disease models with potential clues for scientific research. Besides the patient described by Karavanaki et al (1) and the case we described, we found in the literature another report suggesting the association between papillary thyroid cancer and APS type II (10) . Moreover, it is also worth pointing out that patients with APS type I/II have a nonsignificant increased mortality rate for thyroid cancer, approximately two-fold that expected in healthy subjects (11) .…”
Section: To the Editorsupporting
confidence: 68%
“…In all cases in which APS II syndrome was associated with PTC, Hashimoto's thyroiditis was present. Interestingly, this is the third patient of Southern European origin reported (one from Greece and one from Italy already reported); one other patient comes from Brazil [2][3][4].…”
mentioning
confidence: 67%
“…It has been proposed that women with Hashimoto's thyroiditis are 30% more likely to have coexisting PTC compared with healthy controls [6]. As has been pointed out [4], patients with APS II syndrome and PTC may represent a disease model; under this rationale, it is noteworthy that PTC was diagnosed several years after APS diagnosis in all patients [2][3][4], implying a possible causal effect of autoimmunity.…”
mentioning
confidence: 95%
See 1 more Smart Citation
“…Very few cases of PAS associated with empty sella have been reported in the literature. [10111213] The pathogenesis of empty sella and hypopituitarism is debatable in this case with PAS III. The primary empty sella which is not an uncommon condition, may be considered as a coincidental finding with PAS III.…”
Section: Discussionmentioning
confidence: 94%